Analysis of Efficiency of Use of Factors Production Rice Farming Polluted and Unpolluted By Slaughterhouses Waste In Penggaron Kidul Semarang - Ashilah Zahra Lubis; Bambang Mulyatno Setiawan; Edy Prasetyo (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2021)
Penggaron Kidul is a village in Pedurungan that owns rice fields located around Slaughterhouse (RPH). It causes the rice fields polluted by waste and makes the rice productivity is not optimal. This research aimed to analyze the production factors that affected the amount of rice production, the use of production factors level, and the economic efficiency differences in the use of production factors in polluted and unpolluted fields. The survey method was employed in this research by interviewing the members of Dharma Tani Farmers using a questionnaire. The sampling method used was proportionate stratified random sampling used two populations with 80 people. The number of samples was 66 respondents categorized into 33 farmers (landowners of polluted fields) and 33 farmers (landowners of unpolluted fields). The data analysis conducted using a linear regression analysis method, analysis of Independent Sample T-test, and analysis of technical and economic efficiency then tested using analysis One Sample T-test. The result showed that the use of the land area, labor, and dummy variable of location significantly affected the amount of rice production while the factors of seed, fertilizer, and pesticides did not significantly affect the amount of rice production. The production factors of fertilizer and labor in polluted land had no different from unpolluted fields while the factors of seed and pesticides in polluted fields were different from unpolluted fields. Meanwhile, the production factors of seeds and pesticides in polluted fields were greater than in unpolluted fields. The use of production factors of land area, seeds, fertilizers, pesticides, and labor was technically and economically inefficient. The efficiency economic of production factors in polluted fields is different from unpolluted fields which unpolluted fields are more efficient than polluted fields.